Antibody persistence after two vaccinations with either FSME-IMMUN® Junior or ENCEPUR® Children followed by third vaccination with FSME-IMMUN® Junior - Prymula, Roman; Pöllabauer, Eva Maria; Pavlova, Borislava G; Löw-Baselli, Alexandra; Fritsch, Sandor; Angermayr, Rudolf; Geisberger, Alexander; Barrett, P Noel; Ehrlich, Hartmut J (Human vaccines & immunotherapeutics, 2012)
Tick-borne encephalitis (TBE) vaccination strategies to induce optimal seroprotection in children are under constant evaluation. This multi-center, randomized, controlled, phase III clinical study examined antibody persistence in children aged 1-11 y following two prospectively administered doses of either the FSME-IMMUN® Junior or Encepur Children® vaccines, as well as investigating the immunogenicity, safety and vaccine interchangeability of a third vaccination with FSME-IMMUN(®) Junior. A high level of antibody persistence was observed in all subjects 6 mo after the first of two vaccinations with either pediatric TBE vaccine. Based on both immunological tests and viral antigens used, slightly higher seropositivity rates and higher GMCs /GMTs were found in children vaccinated with FSME-IMMUN® Junior compared with those who received Encepur® Children. Seropositivity rates across all age strata combined six months after the first vaccination with FSME-IMMUN® 0.25 mL Junior were 95.1% as determined by Immunozym ELISA, 93.2% as determined by Enzygnost ELISA and 95.3% as determined by NT; compared with 62.6%, 80.5% and 91.0% respectively after vaccination with Encepur® Children. A third vaccination with FSME-IMMUN(®) Junior induced 100% seropositivity in both study groups and was well tolerated as demonstrated by the low rates of systemic and injection site reactions. Subjects who received either FSME-IMMUN Junior® or Encepur(®) Children vaccine for the first two vaccinations and FSME-IMMUN Junior® for the third showed a comparably strong immune response regardless of the previous TBE vaccine administered, demonstrating that two vaccinations with Encepur® Children can successfully be followed by a third vaccination with FSME-IMMUN Junior®.
Keywords: Female; Infant; dítě; předškolní dítě; Viral Vaccines; ženské pohlaví; vakcinace; lidé; virové vakcíny; viry klíšťové encefalitidy; Encephalitis Viruses, Tick-Borne; Vaccination; prospektivní studie; Male; kojenec; Prospective Studies; Child, Preschool; Encephalitis, Tick-Borne; Child; mužské pohlaví; klíšťová encefalitida; Humans